عقائد الوہیت:حواشی تفاسیر کی کلامی تعبیرات کا تقابلی مطالعہ: Monotheism: an analytical study of theological interpretations in brief exegeses - Dr. Fariha Anjum (jihat-ul-islam, 2022)
Monotheism is the base of man’s life. our religion is based on this basic theology, so, unless the beliefs are built on the right foundation, we cannot act in the right way. This article is based on analytical study of Urdu brief exegeses written in twentieth century. It presents the theological interpretation of ayah regarding monotheism and proves the distinction and truthfulness of Islam amongst all religions. It also condemns the false beliefs promoted in that era. These brief exegeses are the important source of diversity of arguments on contemporary theological issues and persuading the true beliefs in the context of monotheism. It also motivates the person to adopt good deeds. In short, brief exegeses have a vital role in promoting true beliefs according to Quran and negate the invalid customs and traditions